American Academy of Optometry Microbial Keratitis Think Tank. Issue 3 (March 2021) - Szczotka-Flynn, Loretta B.; Shovlin, Joseph P.; Schnider, Cristina M.; Caffery, Barbara E.; Alfonso, Eduardo C.; Carnt, Nicole A.; Chalmers, Robin L.; Collier, Sarah; Jacobs, Deborah S.; Joslin, Charlotte E.; Kroken, Abby R.; Lakkis, Carol; et al.
Abstract : SIGNIFICANCE: Think Tank 2019 affirmed that the rate of infection associated with contact lenses has not changed in several decades. Also, there is a trend toward more serious infections associated with Acanthamoeba and fungi. The growing use of contact lenses in children demands our attention with surveillance and case-control studies. PURPOSE: The American Academy of Optometry (AAO) gathered researchers and key opinion leaders from around the world to discuss contact lens–associated microbial keratitis at the 2019 AAO Annual Meeting. METHODS: Experts presented within four sessions. Session 1 covered the epidemiology of microbial keratitis, pathogenesis of Pseudomonas aeruginosa, and the role of lens care systems and storage cases in corneal disease. Session 2 covered nonbacterial forms of keratitis in contact lens wearers. Session 3 covered future needs, challenges, and research questions in relation to microbial keratitis in youth and myopia control, microbiome, antimicrobial surfaces, and genetic susceptibility. Session 4 covered compliance and communication imperatives. RESULTS: The absolute rate of microbial keratitis has remained very consistent for three decades despite new technologies, and extended wear significantly increases the risk. Improved oxygen delivery afforded by silicone hydrogel lenses has not impacted the rates, and although the introduction of daily disposable lenses has minimized the risk of severe disease, there is no consistent evidence that they have altered the overall rate of microbial keratitis. Overnight orthokeratology lenses may increase the risk of microbial keratitis, especially secondary to Acanthamoeba, in children. Compliance remains a concern and a significant risk factor for disease. New insights into host microbiome and genetic susceptibility may uncover new theories. More studies such as case-control designs suited for rare diseases and registries are needed. CONCLUSIONS: The first annual AAO Think Tank acknowledged that the risk of microbial keratitis has not decreased over decades, despite innovation. Important questions and research directions remain.